Pengaruh Corporate Social Responsibility, Mekanisme Good Corporate Governance, Nilai Perusahaan, Ukuran Perusahaan dan Leverage terhadap Return Saham - Sari Octavera; Febri Rahadi (JURNAL PUNDI, 2017)
Corporate Social Responsibility (CSR) represents the role and concern of the company towards the social and environmental aspects related to the operations of the company that interacts with the environment and society and the efforts towards sustainable development. In addition, no less important in the company's operations and its relation in meeting stakeholder trust and stimulating investors to invest is the emphasis on Corporate Governance (GCG) mechanisms in achieving good corporate governance. Implementation of Corporate Social Responsibility and Corporate Governance mechanism and corporate image, as seen from the company's value (Tobin's Q), Company Size (LnSIZE) and Leverage (DER) will help achieve the objectives of establishing the company and improve the welfare of its owner or shareholder by increasing stock return. The sample of this research is 10 oil palm plantation sub-sector period 2012-2014 period. Testing simultaneously shows CSR, Managerial Ownership, Institutional Ownership, Corporate Value, Size and Leverage effect on stock return of 24.4%. Partially, CSR, managerial ownership and corporate value have a negative effect while institutional ownership has a positive effect on stock return. However, these findings have not been shown to have a significant effect. Meanwhile, firm size and leverage proved to have a positive and significant effect on stock return. Keywords: Corporate Social Responsibility, Good Corporate Governance, Firm Value, Firm Size, Leverage, Stock Return.